2019
DOI: 10.1007/s10120-019-00931-1
|View full text |Cite
|
Sign up to set email alerts
|

Internal hernia after gastrectomy for gastric cancer in minimally invasive surgery era

Abstract: Background The incidence and clinical presentation of internal hernia after gastrectomy have been changing in the minimally invasive surgery era. This study aimed to analyze the clinical features and risk factors for internal hernia after gastrectomy for gastric cancer. Methods We retrospectively analyzed internal hernia after gastrectomy for gastric cancer in 6474 patients between January 2003 and December 2016 at Seoul National University Bundang Hospital. Multivariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 29 publications
(45 reference statements)
8
36
0
Order By: Relevance
“…The analysis of the risk factors for IH and SIH additionally validated these ndings. Our results were consistent with those of previous studies 9, 20,24 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The analysis of the risk factors for IH and SIH additionally validated these ndings. Our results were consistent with those of previous studies 9, 20,24 .…”
Section: Discussionsupporting
confidence: 94%
“…The overall rate of IH was 0.8% in our study, and it ranged from 0.19-5% in previous studies 1,7,8,20 . The rate of IH varied greatly among different literatures.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…There are reports that a laparoscopic approach, non-closure of mesenteric defects, and low BMI are independent risk factors for internal hernia by multivariate analysis [5.13.14.15]. One study reported a higher incidence of internal hernia after single-port surgery compared to multi-port surgery, resulting from the relatively difficult manipulation of laparoscopic instruments in single-port surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…Internal hernia occurs in 2% to 5% of patients who undergo gastrectomy with Roux-en-Y reconstruction, leading to the development of critical morbidity. [1][2][3][4][5] Internal hernia developing after gastrectomy with Roux-en-Y reconstruction through the antecolic route occurs by intestinal invagination into two defects: the jejuno-jejunal mesenteric defect, which is formed by the jejunal mesenteries of the Roux limb and afferent limb after jejuno-jejunal anastomosis, and Petersen's defect, which is formed by the jejunal mesentery of the Roux limb and the transverse colic mesentery. 6 Previous studies recommended closure of both the jejuno-jejunal mesenteric defect and Petersen's defect to prevent internal hernia after gastrectomy with Roux-en-Y reconstruction.…”
mentioning
confidence: 99%